Compact Silicon Slot Waveguide Intersection Based on Mode Transformation and Multimode Interference - Kyoung-Soo Kim; Quoc Viet Vuong; Yonghan Kim; Min-Suk Kwon (IEEE Photonics Journal, 2017)
Silicon slot waveguide intersections are necessary for photonic-integrated circuits based on silicon slot waveguides. We theoretically investigate a compact silicon slot waveguide intersection, which consists of mode transformers and a multimode strip waveguide crossing. The mode transformer before the crossing converts the slot waveguide mode into strip waveguide modes with amplitudes and phases appropriate for efficient operation of the crossing, which is based on multimode interference. The reverse conversion happens in the mode transformer after the crossing. The investigated intersection has a throughput of −0.078 dB, a crosstalk of −41 dB, and a footprint of 79.2 μm2. Its properties are better than those of previous silicon slot waveguide intersections, and especially its footprint is less than 33% of the previous ones. The intersection may be used for matrix switches based on silicon slot waveguides.